The IPv6 Debacle: A cautionary tale for all technologists - Dell, Peter (IEEE, 2019)
The Internet community has long known that the dominant network layer protocol, IPv4, could not scale to support the levels of Internet growth that became expected during the late 1980s and early 1990s, and yet the replacement protocol IPv6 has not achieved widespread use. This presentation argues that the dual-stacking transition technique did not adequately consult non-technical perspectives and as a consequence was always unlikely to succeed. This has led to the present-day situation in which the number of Internet-connected devices vastly outnumbers the address space, in which work-arounds or “kludges” are used to eke out more and more connectivity from the IPv4 address space, and in which Internet governance policies have been changed to allow markets in which IPv4 address space is traded between organisations to operate. And yet although these markets were expected to facilitate the movement of address space from highly-allocated to relatively lower-allocated economies – which are generally in developing countries – yet the limited evidence available suggests that address space is rarely traded across national boundaries. Are these policies effective? Are we repeating the mistake of not consulting diverse perspectives?